“THE ROLE OF THE ENGLISH LANGUAGE IN OUR DAILY LIFE” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
English has become a central tool in daily life, particularly in global communication, education, technology, and media environments. This article analyzes how proficiency in English facilitates access to digital media platforms, content creation, international news, online learning, and virtual collaboration. Special attention is given to English as a medium in global broadcasting, social media, and multimedia communication. English proficiency enhances media literacy, enables cross-cultural interactions, and provides professional and personal advantages in an increasingly interconnected world.